Foker technique for esophageal reconstruction after cervical esophagostomy - Giovana Camargo de Almeida; Luiz Roberto Farion de Aguiar; Amanda Ginani Antunes; Aluisio Augusto Belmino Gadelha (Elsevier, 2021)
The approach to patients with complicated esophageal atresia continues to be a challenge for the pediatric surgeon. Patients with long-gap esophageal atresia (LGEA) or who had complications during their first surgery may require cervical esophagostomy and gastrostomy for posterior definitive correction. Usually reconstruction is performed through esophageal replacement with gastric, ileal, or colonic interposition. This paper reports on two cases in which the intraoperative stretching technique - Foker - maintaining the native esophagus was used, for reconstruction of the digestive tract in patients submitted to cervical esophagostomy and gastrostomy at birth, one due to diagnosis of LGEA and the other due to complications in the primary correction.